Optimization Model of Raw Material Selection Process for Complex Industry Based on Improved Sequential Quadratic Programming Algorithm - He, Xiuli; Zhang, Yang; Hong, Mengna; Li, Jigeng (International journal of computational intelligence systems, 2022)
Raw materials for industrial production mainly come from nature with wide sources and uneven quality, while production requires strictly with the materials’ quality and their quality indicators are very mutual coupling. In actual production, unreasonable combination and formula often exist in the process of raw material selection, impeding the improvement of production efficiency, quality, energy-saving, and emission reduction. Unfortunately, research on this actual issue is currently vacant, so the main object of this paper is to address the selection of raw materials and formulations in actual production. Based on the designed logical combination algorithm and improved SQP algorithm, this study established the batch combination model and formula calculation model from the perspective of optimal combination and formula. Finally, a practical example of actual production is given to demonstrate the utility and application of this research.